Validation of a Field Based Chromatin Dispersion Assay to Assess Sperm DNA Fragmentation in the Bottlenose Dolphin (Tursiops truncatus). Issue 5 (11th August 2014) - Sánchez‐Calabuig, M‐J; López‐Fernández, C; Martínez‐Nevado, E; Pérez‐Gutiérrez, JF; de la Fuente, J; Johnston, SD; Blyde, D; Harrison, K; Gosálvez, J
Contents Over the last two decades, there have been significant advances in the use of assisted reproductive technology for genetic and reproductive management of captive dolphin populations, including evaluation of sperm DNA quality. This study validated a customized sperm chromatin dispersion test (SCDt) for the bottlenose dolphin (Tursiops truncatus) as a means of assessing sperm DNA damage both in the field and in the laboratory. After performing the SCDt, two different sperm morphotypes were identified: (i) sperm with fragmented DNA showed large haloes of dispersed DNA fragments emerging from a compact sperm nucleoid core and (ii) sperm containing non‐fragmented DNA displayed small compact haloes surrounded by a dense core of non‐dispersed DNA and protein complex. Estimates of sperm DNA fragmentation by means of SCDt were directly comparable to results obtained following a two‐tailed comet assay and showed a significant degree of correlation (r = 0.961; p < 0.001). This investigation also revealed that the SCDt, with minor modifications to the standard protocol, can be successfully conducted in the field using a LED florescence microscopy obtaining a high correlation (r = 0.993; p = 0.01) between the data obtained in the laboratory and in the field.